Potential Therapeutic Role for Apelin and Related Peptides in Diabetes: An Update. (February 2022) - Palmer, Ethan S; Irwin, Nigel; O'Harte, Finbarr PM
Type 2 diabetes mellitus (T2DM) is an epidemic with an ever-increasing global prevalence. Current treatment strategies, although plentiful and somewhat effective, often fail to achieve desired glycaemic goals in many people, leading ultimately to disease complications. The lack of sustained efficacy of clinically-approved drugs has led to a heightened interest in the development of novel alternative efficacious antidiabetic therapies. One potential option in this regard is the peptide apelin, an adipokine that acts as an endogenous ligand of the APJ receptor. Apelin exists in various molecular isoforms and was initially studied for its cardiovascular benefits, however recent research suggests that it also plays a key role in glycaemic control. As such, apelin peptides have been shown to improve insulin sensitivity, glucose tolerance and lower circulating blood glucose. Nevertheless, native apelin has a short biological half-life that limits its therapeutic potential. More recently, analogues of apelin, particularly apelin-13, have been developed that possess a significantly extended biological half-life. These analogues may represent a promising target for future development of therapies for metabolic disease including diabetes and obesity.